The Influence of Korean Wave, E-WOM, and Brand Awareness on Purchase Interest of Korean Skincare Products Brand Innisfree Among Gen Z - Rohadatul Aisy; Akhmad Saufi (LP2M IAIN Palopo, 2026)
The skincare industry in Indonesia is growing rapidly driven by Gen Z's interest in K-Beauty due to the influence of the Korean Wave, but Innisfree experienced a decline in sales after its 2024 rebranding due to intense competition. This study aims to analyze the influence of the Korean Wave, Electronic Word-of-Mouth (E-WOM), and Brand Awareness on the purchase interest of Innisfree skincare products among Gen Z in Mataram City. Using a causal associative quantitative approach, primary data were collected through an online Likert-scale questionnaire from 100 Gen Z respondents (aged 17-28) with purposive sampling, analyzed by SPSS multiple linear regression after testing validity, reliability, and classical assumptions. The results show that the Korean Wave (β = 0.249, p = 0.036) and E-WOM (β = 0.634, p = 0.000) have a positive and significant effect on purchase interest, while Brand Awareness (β = 5.650, p = 0.087) has a positive but insignificant effect; simultaneously explained 74.9% of the variation (Adj. R²=0.749). In conclusion, E-WOM was the most dominant, so Innisfree needs to prioritize digital reviews and cultural endorsements for market recovery